An interdisciplinary consensus on the management of brain metastases in patients with renal cell carcinoma. (16th June 2022) - Hasanov, Elshad; Yeboa, Debra Nana; Tucker, Mathew D.; Swanson, Todd A.; Beckham, Thomas Hendrix; Rini, Brian; Ene, Chibawanye I.; Hasanov, Merve; Derks, Sophie; Smits, Marion; Dudani, Shaan; Heng, Daniel Y. C.; et al.
Abstract: Brain metastases are a challenging manifestation of renal cell carcinoma. We have a limited understanding of brain metastasis tumor and immune biology, drivers of resistance to systemic treatment, and their overall poor prognosis. Current data support a multimodal treatment strategy with radiation treatment and/or surgery. Nonetheless, the optimal approach for the management of brain metastases from renal cell carcinoma remains unclear. To improve patient care, the authors sought to standardize practical management strategies. They performed an unstructured literature review and elaborated on the current management strategies through an international group of experts from different disciplines assembled via the network of the International Kidney Cancer Coalition. Experts from different disciplines were administered a survey to answer questions related to current challenges and unmet patient needs. On the basis of the integrated approach of literature review and survey study results, the authors built algorithms for the management of single and multiple brain metastases in patients with renal cell carcinoma. The literature review, consensus statements, and algorithms presented in this report can serve as a framework guiding treatment decisions for patients. CA Cancer J Clin. 2022;72:454‐489.